If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + n = 3 Reorder the terms: n + 2x = 3 Solving n + 2x = 3 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2x' to each side of the equation. n + 2x + -2x = 3 + -2x Combine like terms: 2x + -2x = 0 n + 0 = 3 + -2x n = 3 + -2x Simplifying n = 3 + -2x
| 95+52a=303 | | y=x^2-11x+20 | | 0.5x+0.4=0.08x-0.5 | | 5b+20=1.75 | | 6x-4=3x-28 | | 3x^2+23=4 | | -3+t=19 | | -4(3x-9)+6(2x+7)= | | 36-(2c+3)=2(c+4)+c | | v=3.14h | | 4y-25=15 | | 7x+8=107-2x | | 9+4x-5=-8 | | 7s^2+48s-7= | | 8+3x=x+2 | | 7+22=33-4 | | -84=7(-5-x) | | 9b+8b-13=106 | | 4x+2=y | | 3(x+5)+2(4x-7)= | | -(4x+6)=40 | | -44=10x-x-1 | | 15-15(-7-11x)=-13(16-19x) | | 4(2X+5)-4X=4(4x+5) | | 4y^2+20y+20=0 | | 2(x-4)+3=6x-4(1+x) | | 4a+6=3a+6 | | -8+-n+14=6 | | -2(-9+n)=10 | | -3(9-5X)=-4 | | 4(m+3)=36 | | 10-2z=2 |